Factor antropométrico aplicado al diseño de monturas oftálmicas mediante escaneo e impresión 3D. - Sarzosa García, Karina Elizabeth (2019)
The following project focuses on students and teachers from Applied Sciences and Engineering Department in Cotopaxi Technical University in Latacunga city Ecuador. The majority of them require a regular use of glasses due to multiple vision issues. Since glasses are a device used frequently, it is evident various specific problems they can cause. This fact, due to the standard size and weight under which glasses are manufactured. It results in discomforts such as pain and pressure marks over face areas and the head (nasal bone, temporal bone, temple and nape). The project aims to design a prototype of eyeglasses frame based on anthropometric factors taken from three dimensional (3D) scanning. One of the methodologies used was a survey to clearly understand the customer's needs. Once the survey was completed, a person was selected to determine the roots of his problems due to the commercial frame he usually uses. To do so, a 3D scanning was run with the person to acquire real measurements. At the end of the process, the new frame fitted precisely the head shape of the individual. Part of the process involved a software package were several parameters for the design were chosen (color, size, customizing). After the draft version of the frame was obtained using a 3D printer, the feedback was applied with the individual. Basically, from the 3D scanning, a nonsymmetrical facial characteristic was detected. By comparing the commercial eyeglasses frame with the customized one, the origin of the problem was concluded.